# math

posted by .

how do you factor problems like (w^3)(x^2)-(10w^3)(x)+25w^3?

• math -

(w^3)(x^2)-(10w^3)(x)+25w^3?
first factor out w^3
w^3 [ x^2 -10x +25 ]
w^3 (x-5)(x-5)

## Similar Questions

1. ### Math

Factor Completely: I am really confused on how to start it. 12q^5w^2-36q^4w^3-120q^3w^4 Help please. :) Factor out 12q^3w^2: 12q^3w^2(q^2 - 3qw - 10w^2) Can we factor further?
2. ### algebra

Did I do this problem right? (2y+5w+6)(5y+5w-4) 2y(5y)+ 2y(5w) + 2y(-4) + 5w(5y) + 5w(5w)+ 5w(-4) + 6(5y) + 6(5w) + 6(-4) then I multiplied: 10y^2 + 10wy - 8y + 25wy + 25w^2 - 20w + 30y + 30w - 24 then I combined like terms: 10y^2

4. ### math

(Y+3)^2/5+4(Y+3)^7/5=0 solve this equation by factoring. I don't know how to factor problems like this

how do I work out problems such as 3w - 10w?
6. ### algebra

2/w+ 4/w-1 = 10/w(w-1) 2(w-1)/w(w-1) + 4w/w(w-1)=10/w(w-1) 2w-2/w(w-1 +/4w/w(w-1= 10(w-1)/w(w-1) 2w-2+4w=10w-10 2w+4w-10w=-10-2 6w-10w=-10-2 -4w=8 w=2
7. ### Math

Which algebretic equation correct represents this sentence?
8. ### algebra

Divide (-5w^10 + 10w^8+5w^6) / (5w^5) the answers are -w^5 + 5w^3 = w -5w^5 + 10w^8 + w -w^5 +10^8+ 5w^6 and -w^5 + 2w^3 + w
9. ### math

Simplify the expression 23w^3-5w^2x+8wx^2-8w^3-13wx^2+30w^2x Group like terms so: 23w^3-8w^3= 15w^3 -5w^2x+30w^2x= 25w^2x 8wx^2-13wx^2 = -5wx^2 The final answer I got is: 15w^3+25w^2x-5wx^25wx Is this right?
10. ### Math

5.Simplify x/6x-x^2 a)1/6-x ; where x=0.6 b) 1/6-x; where x=6*** c)1/6x; where x=0 d)1/6 6. 5x^3/7x^3+x^4 a)5/7+x; where x= 0,-7**** b)5/7+x; where x=-7 c)5/7x; where x=0 d)5/7 7.x-2/x^2+4x-12 a)1/6+x; where x=-6*** b)1/6+x; where …

More Similar Questions